CFD simulation of temperature distribution and heat transfer pattern inside C492 combustion furnace - Amar Al-Fatah, Ahmad (2009)
Studies into the temperature distribution and heat transfer characteristics in a C492 combustion test furnace using commercial code FLUENT is presented in this paper. The mathematical model is based on an Eulerian description for the continuum phase and the model predicts gas flows, species concentrations and temperatures, particle trajectories and combustion and radiation heat fluxes. The gas phase conservation equations of momentum, enthalpy and mixture fraction are solved utilizing the k-ε turbulence model. Non premix combustion approach is used to predict the combustion process. The composition of the fuel component is setup using probability density function (PDF). A 3-D simplified model is created to determine the temperature and heat flux profiles and other thermal characteristics for a typical 150kW utility furnace firing liquid fuels or gaseous fuels. The temperature profiles of the furnace based on excess air ratio are predicted using the 3-D model. The main parameter is the excess air ratio consists of 1.248, 1.299, 1.362 and 1.417 which is used to study the temperature distribution. The model calculations showed a good agreement with the measured experimental data both in full and pilot scale of the test furnace as well as from the literature data. Using the experience gained from these CFD model studies can potentially improve the operation of a furnace, designing better combustion chamber or furnace with high performance and efficiency. Ultimately, these CFD model has the advantages of reduced cost, time and ability to optimize design significantly without much investment in the real experiment